Estrogen Up-regulates ATBF1 Transcription but Causes Its Protein Degradation in Estrogen Receptor-α-positive Breast Cancer Cells - Dong, Xue-Yuan (American Society for Biochemistry and Molecular Biology, 2011)
The proper level of estrogen-estrogen receptor (ER) signaling is important for the maintenance of epithelial homeostasis in the breast. In a previous study we demonstrated that ATBF1, which has been suggested as a tumor suppressor in breast cancer, inhibited estrogen-mediated cell proliferation by selectively competing with AIB1 for binding to the ER. However, the expression of ATBF1 mRNA was shown to positively correlate with ER in breast cancer specimens. We, therefore, examined whether estrogen regulates ATBF1. We demonstrated that estrogen up-regulated the transcription of ATBF1, which was mediated by the direct binding of the ER onto the ATBF1 promoter, and that a half-estrogen-responsive element in the ATBF1 promoter was essential for ER direct binding. Furthermore, we found that estrogen at lower levels increased, but at higher levels decreased the expression of ATBF1 protein, which involved the degradation of ATBF1 protein by the estrogen-responsive proteasome system. ATBF1 protein levels fluctuate with estrogen levels. Although lower levels of estrogen increased ATBF1 protein expression, ATBF1 still inhibited cell proliferation caused by lower levels of estrogen. These findings not only reveal an autoregulatory feedback loop between ATBF1 and estrogen-ER signaling but also suggest that ATBF1 plays a role in both the maintenance of breast epithelial homeostasis and breast tumorigenesis caused by elevated estrogen levels.